Towards an optimal green tax framework in Malaysia: an exploratory study / Natrah Saad, Zaimah Zainol Ariffin and Abdul Salam Mas’ud - Saad, Natrah; Zainol Ariffin, Zaimah; Mas’ud, Abdul Salam (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
The use of tax legislations to encourage sustainability is not an uncommon exercise worldwide (such as in Europe and the US). While it can actually be implemented by providing incentives (for non-polluters) or imposing penalties (for polluters), the use of both carrot and stick approach has been claimed to be the more meaningful and fair approach to industry players and society at large. Malaysia has to date, adopted only the incentives approach in its effort to encourage a green environment. However, evidence of the positive impacts of this kind of approach is not discernible, considering the alarming level of environmental abuse reported in the media nowadays. Hence, this study proposed an optimal green tax framework as an alternative to the current practice, based on interviews with policymakers and industry players. The proposed framework suggests that in order to have an optimal green tax initiative, it should consider the elements of tax penalties, tax incentives, environmental education, continual review of legislation and technology/innovation. As an implication for future research, the study recommends that researchers consider a survey involving a larger group of stakeholders (including representatives from the community and non-governmental organisations) for empirical validation and testing of the framework.